Zirconium oxide ceramic filter based on vacuum stirring and supercritical rubber discharging

By using technical means such as vacuum stirring and supercritical CO2 fluid extraction during the preparation of ceramic filters, the problem of insufficient performance of traditional ceramic filters is solved, and the preparation of high-performance zirconia ceramic filters is realized.

CN119455529APending Publication Date: 2025-02-18SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411413716.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional domestic ceramic filters have problems such as high impurity content, low porosity, low high temperature strength and poor thermal shock resistance, and cannot meet the technical requirements of high-temperature alloy precision casting.

Method used

Zirconia ceramic filters are prepared by a process based on vacuum stirring and supercritical glue discharge. The specific steps include hydrolyzing the foam ceramic precursor in sodium hydroxide solution to form a three-dimensional web structure; stirring Mg-stable high-purity zirconia ceramic powder, lignin and other materials under vacuum to prepare ceramic slurry; The ceramic filter blank is formed by impregnation, extrusion and centrifugation; the ceramic filter is extracted and calcined with supercritical CO2 fluid to remove low molecular organic matter and stabilize the ceramic crystal structure.

Benefits of technology

The prepared zirconia ceramic filter has low impurity content, high porosity, high temperature resistance, good thermal shock resistance, and reaches or exceeds the performance indicators of the same technical level abroad.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention designs a zirconia ceramic filter based on vacuum stirring and supercritical rubber discharging, which is prepared by the following steps: S1, immersing a foamed ceramic precursor into a sodium hydroxide solution for hydrolysis treatment, washing with clear water, and airing; s2, selecting Mg-stable high-purity zirconia ceramic powder, lignin, a plasticizer, a surfactant and a dispersing agent, and stirring in a vacuum state to prepare ceramic slurry; s3, immersing the foamed ceramic precursor into the ceramic slurry, vacuumizing and immersing for a period of time, and then carrying out extrusion treatment and centrifugal treatment to obtain a ceramic filter blank; s4, extracting the ceramic filter green body by using CO2 to obtain a ceramic filter matrix; s5, carrying out calcination treatment on the ceramic filter matrix; therefore, the zirconia ceramic filter with low impurity content, high porosity, high temperature resistance and good thermal shock resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic filters, and in particular relates to a zirconia ceramic filter based on vacuum stirring and supercritical debinding. Background Art

[0002] Ceramic filters for high-temperature alloy precision casting have been widely used as auxiliary materials for precision casting in high-temperature alloy precision casting technology. Since the ceramic filter has a high porosity, excellent high-temperature properties such as high-temperature thermal shock resistance and high-temperature bending strength, and has a three-dimensional network skeleton structure and through pores, the use of ceramic filters to filter and purify the molten metal during the high-temperature alloy precision casting process can efficiently remove large inclusions and fine suspended inclusions in the molten metal through mechanical blocking, rectifying slag, surface adsorption and other mechanisms, and promote the precipitation of some gases, which can ultimately significantly reduce the inclusion content of high-temperature alloy precision castings and effectively improve the mechanical properties and service life of high-temperature alloy precision castings;

[0003] At present, traditional domestic ceramic filters have problems such as high impurity content, low porosity, low high temperature strength, and poor thermal shock resistance, and cannot meet the technical requirements of high temperature alloy precision casting;

[0004] Therefore, it is necessary to carry out research on the preparation technology of domestic ceramic filters. Our company has developed a zirconia ceramic filter based on vacuum stirring and supercritical debinding. The filter has low impurity content, high porosity, high temperature resistance, and good thermal shock resistance. It can reach the same technical level as foreign countries or have better technical indicators in some aspects. It is a series of domestic high-performance, low-cost ceramic filters for high-temperature alloy precision casting. Summary of the invention

[0005] The invention designs a zirconia ceramic filter based on vacuum stirring and supercritical debinding, which comprises the following steps: S1: immersing a foam ceramic precursor in a sodium hydroxide solution, then performing a hydrolysis treatment, and drying after the water treatment; S2: selecting Mg-stabilized high-purity zirconia ceramic powder, lignin, a plasticizer, a surfactant, and a dispersant, and stirring them under a vacuum state to prepare a ceramic slurry; S3: immersing the foam ceramic precursor in the ceramic slurry, and after vacuum impregnation for a period of time, performing an extrusion treatment and a centrifugal treatment to obtain a ceramic filter blank; S4: extracting the ceramic filter blank using a supercritical CO2 fluid to obtain a ceramic filter matrix; S5: calcining the ceramic filter matrix.

[0006] Compared with the prior art, the beneficial effects of the present invention are as follows: by immersing the foam ceramic precursor in a sodium hydroxide solution, the inter-network membrane on the foam ceramic precursor can be removed, and by repeatedly rinsing and rubbing with clean water to remove the removed inter-network membrane and the sodium hydroxide solution, the ceramic precursor forms a three-dimensional grid structure, and the organic precursor is selected to have strong hydrophilicity, uniform pores, high porosity, high elasticity, and high tensile strength, and the pores are through holes and the inter-network membrane is small; by selecting the mutual relationship between the wetting ability of Mg-stabilized high-purity zirconia ceramic powder and the organic polymer and the external mechanical force, a slurry with good uniformity and good fluidity is prepared; by immersing the foam ceramic precursor in the ceramic slurry, the ceramic slurry can be evenly dispersed on the three-dimensional network structure of the foam ceramic precursor, and after vacuum impregnation for a period of time, extrusion is performed. The pressure treatment can make the slurry evenly coated on the precursor, and then the excess slurry is removed during rotation through centrifugal treatment, so that the slurry can be coated on the precursor more evenly; the low-molecular organic matter in the slurry of the ceramic filter is extracted by supercritical CO2 fluid, and the ceramic slurry is initially debonded at low temperature, so that the low-molecular organic matter is converted into gas and discharged; the calcination treatment after extraction can extract the low-molecular organic matter in the slurry and foam ceramic precursor, burn the large-molecular and high-molecular organic matter, and burn the organic matter in the foam ceramic precursor at the same time, and at the same time avoid drastic volume changes of ceramics during sintering, control the stable changes of ceramic crystal structure, avoid ceramic cracking, and fully sinter. The sintered zirconia ceramic filter has low impurity content, high porosity, high temperature resistance and good thermal shock resistance.

[0007] Furthermore, the concentration of the sodium hydroxide solution in S1 is 8%-12%, the water treatment temperature is 45° C.-55° C., and the hydrolysis treatment time is 3.8 h-4.2 h.

[0008] The beneficial effect of adopting the above-mentioned further technical scheme is that by immersing the foam ceramic precursor in a sodium hydroxide solution with a concentration of 8%-12%, the inter-network membrane on the foam ceramic precursor can be removed, and by repeatedly rinsing and rubbing with 45°C-55°C clean water to remove the removed inter-network membrane and sodium hydroxide solution, the ceramic precursor forms a three-dimensional grid structure, and after drying, the foam ceramic precursor can have strong hydrophilicity, uniform pores, high elasticity, high tensile strength and high porosity.

[0009] Furthermore, the plasticizer in S2 is one of cocoamide (CMEA), polyethylene glycol (PEG), and polyvinyl butyral (PVB), the surfactant is stearic acid (SA), and the dispersant is polyacrylamide.

[0010] The beneficial effect of adopting the above-mentioned further technical scheme is that: by adding plasticizers, surfactants and dispersants to the ceramic powder, zirconia ceramics with uniform flow and dispersion can be prepared, which can be better applied and infiltrated onto the ceramic precursor. The plasticizers and surfactants can increase the degree of adhesion of the ceramic powder on the ceramic precursor, so that the ceramic powder is evenly hung on the ceramic precursor. The dispersant can improve the dispersibility of the ceramic powder in the slurry, so that the slurry flows evenly, disperses evenly, and has good bonding with the ceramic precursor with a three-dimensional network structure.

[0011] Furthermore, the weight ratio of the Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant, and dispersant in the S2 is: 78-84: 13-16: 3.4-3.9: 0.2-0.7.

[0012] Furthermore, the preparation process of the Mg-stabilized high-purity zirconium oxide ceramic powder in S2 is as follows: dissolving zirconium oxychloride in deionized water, filtering, adding 2.2%-8% magnesium oxide, stirring at a speed of 35RPM-45RPM, stirring and mixing for 0.5h-2h, and obtaining a chloride solution;

[0013] Add a precipitant to the chloride solution, wherein the precipitant is ammonia water, the pH of the ammonia water is greater than 10, and the molar ratio of NH3 to Mg2++Zr2+ is 1.2-2:1, stir for 10min-30min, precipitate, filter and remove the liquid to obtain a precipitate;

[0014] The precipitate is washed with ammonia water, dried at 100°C-120°C for 10h-24h, heated to 450°C-500°C, kept warm for 1h-2h, heated to 580°C-650°C, kept warm for 2h-4h, and a Mg-stabilized high-purity zirconium oxide powder is prepared;

[0015] The particle size D50 of the Mg-stabilized high-purity zirconia ceramic in the S2 is 1.8 μm-2.3 μm.

[0016] The beneficial effect of adopting the above-mentioned further technical scheme is that it is prepared by precipitation, washing and heating of zirconium oxychloride and magnesium oxide, so as to form a stable crystalline structure, which can make magnesium stably control the crystal phase change of zirconium during the later sintering process, and by adding Mg-stabilized high-purity zirconium oxide ceramic powder, magnesium is doped into the zirconium lattice, which can ensure the stability of zirconium during the phase change process, ensure the uniform phase change, avoid drastic phase change when the temperature changes drastically, avoid changes back and forth between low and high temperatures, make the ceramic grains undergo phase change in a stable state, make the expansion coefficient of the ceramic grains consistent, avoid the problem of ceramic slurry cracking, enhance thermal properties, enhance the thermal shock resistance of the finished product, form a stable phase, make the ceramic powder evenly hang on the ceramic precursor, and make the zirconium oxide ceramic powder evenly coated on the ceramic precursor through the reasonable ratio of lignin, dispersant, plasticizer, surfactant and dispersant.

[0017] Furthermore, the vacuum pressure in S2 is 0.2MPa-0.6MPa, the stirring speed is 35RPM-45RPM, and the viscosity of the ceramic slurry is 78η / Pa·s-84η / Pa·s.

[0018] The beneficial effect of adopting the above further technical solution is that by stirring the ceramic slurry under vacuum, the viscosity of the ceramic slurry combined with the ceramic precursor can be improved, and the ceramic slurry can be more evenly attached to the ceramic precursor.

[0019] Furthermore, the immersion time in S3 is 3 min-7 min, the pressure of the extrusion treatment is 45 bar-75 bar, and the rotational angular speed of the centrifugal treatment is 10000-23000 rpm.

[0020] The beneficial effect of adopting the above further technical solution is that the ceramic slurry is firmly and evenly attached to the ceramic precursor through extrusion treatment, and the excess slurry can be rotated and removed through centrifugal treatment, so that the slurry is more evenly coated on the precursor.

[0021] Furthermore, the CO2 in S4 is a supercritical CO2 fluid degreasing system for the first extraction and the second extraction, the first extraction pressure of the CO2 is 15MPa-25MPa, the first extraction temperature is 60℃-70℃; the first extraction time is 1h-2.5h, and the first extraction flow rate is 0.3L / h-0.8L / h

[0022] The second extraction pressure of CO2 is 25MPa-35MPa, the second extraction temperature is 70°C-80°C, the second extraction time is 1h-2.5h, and the second extraction flow rate is 0.3L / h-0.8L / h.

[0023] The beneficial effect of adopting the above-mentioned further technical scheme is that by utilizing the supercritical CO2 fluid degreasing system to perform the first extraction of low-molecular organic matter on the slurry part, the low-molecular and polar molecules dissolved in the slurry can be discharged at low temperature, so that the prepared ceramic filter is purer and free of impurities. The first extraction forms small molecular through holes on the slurry of the ceramic filter, and the second extraction allows the large molecular plasticizer organic matter in the slurry to be discharged from the through holes of the first extraction, which is beneficial to avoid the problem of uneven slurry during the debinding process, thereby avoiding the cracking of the ceramic slurry during the extraction process.

[0024] Furthermore, the calcination treatment includes volatilization treatment, phase change uniformization treatment and porcelain formation treatment.

[0025] The beneficial effects of adopting the above-mentioned further technical scheme are: the ceramic slurry and the ceramic precursor are better combined through calcination treatment, the slurry can be initially solidified and debonded during volatilization treatment, and zirconium can stably undergo phase change during phase change uniformization treatment; during porcelain-forming treatment, the ceramic crystals can be prevented from changing too quickly or too slowly, and the ceramic filter can be fully sintered, so that the produced ceramics have good cost-effectiveness and yield rate.

[0026] Furthermore, the temperature of the volatilization treatment is increased from 0°C to 790°C-810°C, the heating rate is 3°C / min-6°C / min, and the holding time is 0.9h-1.1h; the temperature of the phase change uniformization treatment is increased from 790°C-810°C to 1300°C-1320°C, the heating rate is 3°C / min-6°C / min, and the holding time is 0.9h-1.1h; the temperature of the porcelain formation treatment is increased from 1300°C-1320°C to 1550°C-1570°C, the heating rate is 2°C / min-5°C / min, and the holding time is 5.8h-6.2h.

[0027] The beneficial effects of adopting the above-mentioned further technical scheme are: the slurry can be initially solidified during the volatilization treatment, the organic matter remaining after the extraction can be subjected to low-temperature debinding, the organic high molecular components in the slurry and the ceramic precursor can be converted into gas, the generated CO and CO2 can be discharged, and a certain vacancy is generated at the position of the ceramic precursor after debinding to form a three-dimensional network of through holes; through the phase change uniform treatment, the organic solvent in the slurry can be completely volatilized, and the slurry can be phase-changed into ceramic during sintering. During the sintering process, the zirconium temperature rises from 790℃-810℃ to 1300℃ -1320℃ stable phase change occurs to avoid cracking; during the porcelain-forming period, it can further ensure the uniformity of phase change, avoid drastic changes in ceramic grains, avoid abnormal grain growth due to heating too slowly or unevenness due to drastic temperature changes, avoid drastic volume expansion and contraction of ceramics, thereby avoiding cracking of ceramics, making the ceramic grains grow evenly, making the finished product have good thermal properties, which can ensure the performance of porcelain-forming, and make the finished product have low impurity content, high porosity, high temperature resistance, good thermal shock resistance, and at the same time reduce cost and economic benefits. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0029] Embodiment 1:

[0030] The present embodiment provides a zirconia ceramic filter based on vacuum stirring and supercritical debinding, comprising the following steps: S1: immersing a foam ceramic precursor in a sodium hydroxide solution, then performing a hydrolysis treatment, and drying after the water treatment; S2: selecting Mg-stabilized high-purity zirconia ceramic powder, lignin, a plasticizer, a surfactant, and a dispersant and stirring them under a vacuum state to obtain a ceramic slurry; S3: immersing the foam ceramic precursor in the ceramic slurry, vacuuming and impregnating for a period of time, and then extruding and centrifuging to obtain a ceramic filter blank; S4: using a supercritical fluid to heat the ceramic precursor. The ceramic filter blank is extracted by CO2 fluid to obtain a ceramic filter matrix; S5: the ceramic filter matrix is ​​calcined; the inter-network membrane on the foam ceramic precursor can be removed by immersing the foam ceramic precursor in a sodium hydroxide solution, and the removed inter-network membrane and the sodium hydroxide solution are repeatedly washed and rubbed with clean water, so that the ceramic precursor forms a three-dimensional grid structure; by selecting the relationship between the wetting ability of Mg-stabilized high-purity zirconia ceramic powder and the organic polymer and the external mechanical force, a ceramic filter having good uniformity, Slurry with good fluidity; by immersing the foam ceramic precursor into the ceramic slurry, the ceramic slurry can be evenly dispersed on the three-dimensional network structure of the foam ceramic precursor, and after vacuum impregnation for a period of time, it is extruded to allow the slurry to be evenly coated on the precursor, and then the excess slurry is removed during rotation by centrifugal treatment, so that the slurry can be more evenly coated on the precursor; by using supercritical CO2 fluid to extract the low-molecular organic matter in the slurry of the ceramic filter, the ceramic slurry is initially debonded at low temperature, so that the low-molecular organic matter is converted into gas and discharged; The calcination treatment after extraction can extract low molecular weight organic matter in the slurry and the foam ceramic precursor, burn out the macromolecular and high molecular weight organic matter, and burn out the organic matter in the foam ceramic precursor at the same time, and can avoid the drastic volume change of the ceramic during the sintering process, can control the stable change of the ceramic crystal structure, avoid the ceramic cracking, can fully sinter, and after sintering, can form a three-dimensional network of through holes on the foam ceramic precursor, so that the generated foam ceramic precursor can have strong hydrophilicity, uniform pores, high elasticity, high tensile strength and high porosity.

[0031] The concentration of the sodium hydroxide solution in S1 is 10%, the water treatment temperature is 50°C, and the water treatment time is 4 hours; by immersing the foam ceramic precursor in a sodium hydroxide solution with a concentration of 10%, the inter-network membrane on the foam ceramic precursor can be removed, and by repeatedly rinsing and rubbing with 50°C clean water to remove the removed inter-network membrane and sodium hydroxide solution, the ceramic precursor forms a three-dimensional grid structure, and after drying, the foam ceramic precursor can have strong hydrophilicity, uniform pores, high elasticity, high tensile strength, and high porosity.

[0032] The plasticizer in S2 is one of cocoamide (CMEA), polyethylene glycol (PEG), and polyvinyl butyral (PVB), the surfactant is stearic acid (SA), and the dispersant is polyacrylamide; by adding plasticizers, surfactants, and dispersants to ceramic powders, zirconia ceramics with uniform flow and dispersion are prepared, which can be better applied and infiltrated on ceramic precursors. The plasticizers and surfactants can increase the degree of adhesion of ceramic powders on ceramic precursors, so that the ceramic powders are evenly hung on the ceramic precursors. The dispersant can improve the dispersibility of ceramic powders in slurry, so that the slurry flows evenly, disperses evenly, and has good bonding with ceramic precursors with three-dimensional network structures.

[0033] The weight ratio of the Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant and dispersant in the S2 is 81.5:14.24:3.7:0.5.

[0034] The preparation process of the Mg-stabilized high-purity zirconium oxide ceramic powder in S2 is as follows: dissolving zirconium oxychloride in deionized water, filtering, adding 5% magnesium oxide, stirring at a speed of 40 RPM, stirring and mixing for 1.5 hours to obtain a chloride solution;

[0035] The NH3 and Mg 2+ +Zr 2+ The molar ratio of is 1.6:1, stirring for 20 minutes, precipitation, filtration and removal of liquid to obtain a precipitate;

[0036] The precipitate is washed with ammonia water, dried at 110°C for 17h, heated to 475°C, kept warm for 1.5h, heated to 620°C, kept warm for 3h, and Mg-stabilized high-purity zirconium oxide powder is prepared; the Mg-stabilized high-purity zirconium oxide ceramic particle size D50 in the S2 is 2μm; it is prepared by precipitating zirconium oxychloride and magnesium oxide, washing, and heating, so as to form a stable crystalline structure, which can control the crystal phase change of zirconium stabilized by magnesium in the later sintering process, and by adding Mg-stabilized high-purity zirconium oxide ceramic powder, it can be ensured that the ceramic slurry is Stability during the phase change process ensures uniform phase change, avoids drastic phase changes when the temperature changes drastically, avoids changes back and forth between low and high temperatures, allows ceramic grains to undergo phase changes in a stable state, makes the expansion coefficient of ceramic grains consistent, avoids the problem of ceramic slurry cracking, can enhance thermal properties, enhance the thermal shock resistance of the finished product, form a stable phase, and allow ceramic powder to be evenly hung on the ceramic precursor. Through the reasonable ratio of lignin, dispersant, plasticizer, surfactant, and dispersant, zirconia ceramic powder can be evenly applied to the ceramic precursor.

[0037] The vacuum pressure in S2 is 0.4 MPa, the stirring speed is 40 RPM, and the viscosity of the ceramic slurry is 81.4 η / Pa·s. By stirring the ceramic slurry under vacuum, the viscosity of the ceramic slurry combined with the ceramic precursor can be improved, and the ceramic slurry can be more evenly attached to the ceramic precursor.

[0038] The immersion time in S3 is 5 minutes, the pressure of the extrusion treatment is 60 bar, and the rotational angular speed of the centrifugal treatment is 17000 rpm. The extrusion treatment allows the ceramic slurry to be firmly and evenly attached to the ceramic precursor, and the centrifugal treatment can be used to rotate and remove excess slurry, so that the slurry can be more evenly coated on the precursor.

[0039] The first extraction and the second extraction are carried out in the supercritical CO2 fluid degreasing system in S4, the first extraction pressure of CO2 is 25MPa, the first extraction temperature is 65°C; the first extraction time is 1.8h, and the first extraction flow rate is 0.5L / h

[0040] The second extraction pressure of CO2 is 30MPa, the second extraction temperature is 75°C, the second extraction time is 2h, and the second extraction flow rate is 0.5L / h; by utilizing the supercritical CO2 fluid degreasing system to perform the first extraction on the low-molecular organic matter in the slurry part, the low-molecular and polar molecules dissolved in the slurry can be discharged at low temperature, so that the prepared ceramic filter is purer and free of impurities. The first extraction forms small molecular through holes on the slurry of the ceramic filter, and the second extraction allows the large molecular organic matter in the slurry to be discharged from the through holes of the first extraction, which is conducive to avoiding the problem of uneven slurry during the debinding process, thereby avoiding the cracking of the ceramic slurry during the extraction process.

[0041] The calcination treatment includes volatilization treatment, phase change uniformization treatment and ceramic formation treatment. The calcination treatment allows the ceramic slurry and the ceramic precursor to be better combined, the volatilization treatment allows the slurry to be initially solidified and debonded, and the phase change uniformization treatment allows the zirconium to undergo a stable phase change; in the ceramic formation treatment, the ceramic crystals can be prevented from changing too fast or too slowly, and the ceramic filter can be fully sintered, so that the produced ceramics have good cost-effectiveness and yield rate.

[0042] The temperature of the volatilization treatment is increased from 0°C to 800°C, the heating rate is 4°C / min, and the holding time is 1 hour; the temperature of the phase change uniformization treatment is increased from 800°C to 1310°C, the heating rate is 5°C / min, and the holding time is 1 hour; the temperature of the porcelain formation treatment is increased from 1310°C to 1570°C, the heating rate is 3°C / min, and the holding time is 6 hours. During the volatilization treatment, the slurry can be initially solidified, the organic matter remaining after extraction can be debonded at low temperature, the organic high molecular components in the slurry and ceramic precursor can be converted into gas, the generated CO and CO2 can be discharged, and certain vacancies can be generated at the position of the ceramic precursor after debonding to form a three-dimensional network of through holes; through the phase change uniform treatment, the organic solvent in the slurry can be completely volatilized, and the slurry can be phase-changed into ceramic during sintering. During the sintering process, zirconium undergoes a stable phase change at 800℃-1310℃ to avoid cracking; during the ceramic forming period, the phase change can be further guaranteed to be uniform, avoid drastic changes in ceramic grains, avoid abnormal grain growth due to too slow heating or unevenness due to drastic temperature changes, avoid drastic volume expansion and volume contraction of ceramics, thereby avoiding cracking of ceramics, making the ceramic grains grow uniformly, making the finished product have good thermal properties, ensuring the performance of the ceramic, making the finished product have low impurity content, high porosity, high temperature resistance, good thermal shock resistance, and at the same time reducing cost and economic benefits.

[0043] Embodiment 2:

[0044] The same contents as those in the first embodiment are not described in detail here. The differences between the first embodiment and the present embodiment are as follows:

[0045] The concentration of the sodium hydroxide solution in S1 is 9%, the water treatment temperature is 46° C., and the hydrolysis treatment time is 3.9 h.

[0046] The weight ratio of the Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant and dispersant in the S2 is 79:13.5:3.6:0.3.

[0047] The particle size D50 of the Mg-stabilized high-purity zirconia ceramic in the S2 is 1.9 μm.

[0048] The preparation process of the Mg-stabilized high-purity zirconium oxide ceramic powder in S2 is as follows: zirconium oxychloride is dissolved in deionized water, filtered, and then 2.3% magnesium oxide is added, the stirring speed is 36 RPM, and the mixture is stirred for 0.6 h to obtain a chloride solution;

[0049] The NH3 and Mg 2+ +Zr 2+ The molar ratio of is 1.3:1, stirred for 11 minutes, precipitated, filtered and the liquid was removed to obtain a precipitate;

[0050] The precipitate was washed with ammonia water, dried at 101°C for 11 hours, heated to 460°C, kept warm for 1.1 hours, heated to 585°C, kept warm for 2.1 hours, and Mg-stabilized high-purity zirconium oxide powder was prepared; the Mg-stabilized high-purity zirconium oxide ceramic particle size D50 in S2 was 1.9 μm. It was prepared by precipitating zirconium oxychloride and magnesium oxide, washing, and heating;

[0051] The vacuum pressure in S2 is 0.3 MPa, the stirring speed is 36 RPM, and the viscosity of the ceramic slurry is 79 η / Pa·s.

[0052] The immersion time in S3 is 3.5 min, the pressure of the extrusion treatment is 46 bar, and the rotational angular speed of the centrifugal treatment is 11000 rpm.

[0053] The CO2 in S4 is used for the first extraction and the second extraction in a supercritical CO2 fluid degreasing system, the first extraction pressure of the CO2 is 16MPa, the first extraction temperature is 61°C; the first extraction time is 1.1h, and the first extraction flow rate is 0.4L / h;

[0054] The second extraction pressure of CO2 is 26 MPa, the second extraction temperature is 71°C, the second extraction time is 1.1 h, and the second extraction flow rate is 0.4 L / h.

[0055] The temperature of the volatilization treatment is increased from 0°C to 795°C, the heating rate is 3.5°C / min, and the holding time is 0.95h; the temperature of the phase change uniformization treatment is increased from 795°C to 1305°C, the heating rate is 3.5°C / min, and the holding time is 0.95h; the temperature of the porcelain formation treatment is increased from 1310°C to 1555°C, the heating rate is 2.5°C / min, and the holding time is 5.9h.

[0056] Embodiment three:

[0057] The same contents as those of the second embodiment are not described in detail here; the differences between the third embodiment and the present embodiment are as follows:

[0058] The concentration of the sodium hydroxide solution in S1 is 11%, the water treatment temperature is 54° C., and the hydrolysis treatment time is 4.1 h.

[0059] The weight ratio of the Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant and dispersant in the S2 is 83:15:3.8:0.6.

[0060] The particle size D50 of the Mg-stabilized high-purity zirconia ceramic in the S2 is 2.2 μm.

[0061] The preparation process of the Mg-stabilized high-purity zirconium oxide ceramic powder in S2 is as follows: zirconium oxychloride is dissolved in deionized water, filtered, and then 7% magnesium oxide is added, the stirring speed is 44 RPM, and the mixture is stirred for 1.8 hours to obtain a chloride solution;

[0062] The NH3 and Mg 2+ +Zr 2+ The molar ratio of is 1.8:1, stirred for 25 minutes, precipitated, filtered and the liquid was removed to obtain a precipitate;

[0063] The precipitate is washed with ammonia water, dried at 115°C for 23 hours, heated to 490°C, kept warm for 1.8 hours, heated to 640°C, kept warm for 3.8 hours, and Mg-stabilized high-purity zirconium oxide powder is prepared; the Mg-stabilized high-purity zirconium oxide ceramic particle size D50 in the S2 is 2.2 μm; it is prepared by precipitating zirconium oxychloride and magnesium oxide, washing, and heating;

[0064] The vacuum pressure in S2 is 0.5 MPa, the stirring speed is 44 RPM, and the viscosity of the ceramic slurry is 83η / Pa·s.

[0065] The immersion time in S3 is 6 minutes, the pressure of the extrusion treatment is 74 bar, and the rotational angular speed of the centrifugal treatment is 22000 rpm.

[0066] The CO2 in S4 is used for the first extraction and the second extraction in a supercritical CO2 fluid degreasing system, the first extraction pressure of the CO2 is 24MPa, the first extraction temperature is 69°C; the first extraction time is 2.4h, and the first extraction flow rate is 0.7L / h;

[0067] The second extraction pressure of CO2 is 34MPa, the second extraction temperature is 79°C, the second extraction time is 2.4h, and the second extraction flow rate is 0.7L / h;

[0068] The temperature of the volatilization treatment is increased from 0°C to 805°C, the heating rate is 5°C / min, and the holding time is 1.05h; the temperature of the phase change uniformization treatment is increased from 805°C to 1315°C, the heating rate is 5°C / min, and the holding time is 1.05h; the temperature of the porcelain formation treatment is increased from 1310°C to 1560°C, the heating rate is 4°C / min, and the holding time is 6.1h.

[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A zirconia ceramic filter based on vacuum stirring and supercritical debinding, characterized in that: The following steps are involved: S1: immersing the foam ceramic precursor in a sodium hydroxide solution for hydrolysis, rinsing with clean water and then drying; S2: Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant and dispersant are selected and stirred under vacuum to obtain ceramic slurry; S3: The foam ceramic precursor is immersed in the ceramic slurry, and after vacuum impregnation for a period of time, it is extruded and centrifuged to obtain a ceramic filter blank; S4: The ceramic filter blank is extracted with CO2 to obtain a ceramic filter matrix; S5: The ceramic filter matrix is ​​calcined.

2. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in S1 is 8%-12%, the water treatment temperature is 45° C.-55° C., and the hydrolysis treatment time is 3.8 h-4.2 h.

3. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 2, characterized in that: The plasticizer in S2 is one of cocoamide (CMEA), polyethylene glycol (PEG), and polyvinyl butyral (PVB), the surfactant is stearic acid (SA), and the dispersant is polyacrylamide.

4. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 3, characterized in that: The weight ratio of the Mg-stabilized high-purity zirconia ceramic powder, lignin, plasticizer, surfactant and dispersant in the S2 is: 78-84: 13-16: 3.4-3.9: 0.2-0.

7.

5. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 4, characterized in that: The preparation process of the Mg-stabilized high-purity zirconium oxide ceramic powder in S2 is as follows: dissolving zirconium oxychloride in deionized water, filtering, adding 2.2%-8% magnesium oxide, stirring at a speed of 35RPM-45RPM, stirring and mixing for 0.5h-2h to obtain a chloride solution; A precipitant is added to the chloride solution, wherein the precipitant is ammonia water, the pH of the ammonia water is greater than 10, and the NH3 and Mg 2+ +Zr 2+ The molar ratio of is 1.2-2:1, stirring for 10min-30min, and removing the liquid after precipitation and filtration to obtain a precipitate; The precipitate is washed with ammonia water, dried at 100°C-120°C for 10h-24h, heated to 450°C-500°C, kept warm for 1h-2h, heated to 580°C-650°C, kept warm for 2h-4h, and a Mg-stabilized high-purity zirconium oxide powder is prepared; The particle size D50 of the Mg-stabilized high-purity zirconia ceramic in the S2 is 1.8 μm-2.3 μm.

6. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 1, characterized in that: The vacuum pressure in S2 is 0.2MPa-0.6MPa, the stirring speed is 35RPM-45RPM, and the viscosity of the ceramic slurry is 78η / Pa·s-84η / Pa·s.

7. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 1, characterized in that: The immersion time in S3 is 3 min-7 min, the pressure of the extrusion treatment is 45 bar-75 bar, and the rotation angular speed of the centrifugal treatment is 10000-23000 rpm.

8. The zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 1, characterized in that: The CO2 in S4 is used for the first extraction and the second extraction in a supercritical CO2 fluid degreasing system, the first extraction pressure of the CO2 is 15MPa-25MPa, the first extraction temperature is 60°C-70°C; the first extraction time is 1h-2.5h, and the first extraction flow rate is 0.3L / h-0.8L / h; The second extraction pressure of CO2 is 25MPa-35MPa, the second extraction temperature is 70°C-80°C, the second extraction time is 1h-2.5h, and the second extraction flow rate is 0.3L / h-0.8L / h.

9. The zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 1, characterized in that: The calcination treatment in S5 includes volatilization treatment, phase change uniformization treatment and porcelain formation treatment.

10. A zirconia ceramic filter based on vacuum stirring and supercritical debinding according to claim 9, characterized in that: The temperature of the volatilization treatment is increased from 0°C to 790°C-810°C, the heating rate is 3°C / min-6°C / min, and the holding time is 0.9h-1.1h; the temperature of the phase change uniformization treatment is increased from 790°C-810°C to 1300°C-1320°C, the heating rate is 3°C / min-6°C / min, and the holding time is 0.9h-1.1h; the temperature of the porcelain formation treatment is increased from 1300°C-1320°C to 1550°C-1570°C, the heating rate is 2°C / min-5°C / min, and the holding time is 5.8h-6.2h.

Citation Information

Patent Citations

  • Zirconium oxide foamed ceramic filter

    CN101259347A

  • Magnesium-stabilized zirconia foamed ceramic and preparation method thereof

    CN113860910A

  • Supercritical fluid process for dewaxing hot-press ceramics

    CN1397516A

  • Spinel-reinforced magnesium oxide-based foam ceramic filter and preparation method therefor

    US20200306675A1